EFEKTIVITAS PROMOSI MELALUI MEDIA SOSIAL PADA UMKM DI KABUPATEN KEBUMEN - Miftahul Huda; Anton Prasetyo (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2020)
Micro small and Medium Enterprises (MSMEs) are a sector that is very influential on the development of the Indonesian economy. The development of information technology makes it easier for MSMEs to market their products, one of which is through social media. Promotion effectiveness is measured by the AIDA concept (Attention, Interest, Desire, Action). This study aims to: 1) determine the effectiveness of promotions by using the AIDA method on consumer buying interest. 2) find out the most dominant variable influencing the increase in consumer buying interest. The sample in this study were 100 account holders who were active and followed a minimum of 1 MSME account in Kebumen Regency. The method of data analysis uses multiple regression analysis. The results of the study concluded that the effectiveness of promotion through social media on MSMEs in the District was included in the good category. This is evidenced by interest, desire, action variables that have a significant effect on purchasing decisions, while attention factors have no significant effect on purchasing decisions. Interest is the most dominant factor in influencing promotion through social media.